Plant Disease Survey in Libya: II. Physiologic Races of Puccinia graminis var. tritici - MOHAMED, HOSNI A. (The Libyan Journal of Agriculture, 2023)
Samples of rusted wheat and barley plants were collected during three successive years, from the western region of Libya. Stem rust races identified were; in 1971: race 14(28.5% 17(21.4%), 19(28.5%). 21 (7%), and 39 (14.6%); in 1972: race 14(54.5%), 17(9.1%), 19(9.1%), 24(18.2%) and 39(9.1%); and in 1973: race 14(61.9%). 17(4.8%), 19(4.8%), 24(14.2%), 39(4.8%) and 53(9.5%). 17(9.1%), 19(9.1%), 24(18.2%) and 39(9.1%); and in 1973: race 14(61.9%). 17(4.8%), 19(4.8%), 24(14.2%), 39(4.8%) and 53(9.5%)